(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
The evaluation of total phenolic contents, antioxidant properties and antimicrobial activities of four medicinal plants such as Centella asiatica, Holarrhena antidysenterica, Euphorbia hirta, Alstonia scolaris were performed using 80% methanol as a solvent. They were screening out to investigate their phytochemical properties. Preliminary phytochemical studies revealed the presence of flavonoids, alkaloids, glycosides, steroids, phenols, saponins, terpenoid, cardiac glycosides and tannins as the chemical class present in the extracts. The results suggest the phytochemical properties of the plant for curing various ailments. Preliminary antioxidative activities of the samples were also determined and among them we found that Centella asiatica contained highest total poly phenols (77.40 mg GAE/g sample) as well as DPPH radical scavenging activity (88.16%) and reducing power (OD=1.36). This shows that the plant may be potent source of natural antioxidants. The antimicrobial activity can be determined only in Centella asiatica and Holarrhena antidysenterica methanolic extract. However both of them showed considerable level of activity against standard strains and clinical isolates of some gram positive and gram negative bacteria. The obtained results provide a support for the use of these plants in traditional medicine and for its further investigation.